2016
DOI: 10.18632/oncotarget.10082
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA profiles as prognostic biomarkers for HBV-positive hepatocellular carcinoma

Abstract: To establish serum microRNA profiles as prognostic biomarkers in hepatocellular carcinoma patients (HCCs), we used deep sequencing to screen serum microRNAs in a discovery set. Twelve up-regulated serum miRNAs were selected for qPCR analysis in a training set. MiR-192-5p and miR-29a-3p were identified and associated with HCC prognosis. HCCs with high concentrations of miR-192-5p and miR-29a-3p had poorer overall survival (OS) and progression-free survival (PFS) than those with low concentrations. We calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…A recent study proposed that a high concentration of serum miRNA-29a-3p is associated with poor overall survival and progression-free survival in patients with HCC treated with resection or local ablation. 38 However, a contrasting study found miRNA-29 genetic (miRNA-29a-3p/b/c) expression was downregulated in HCC tissue suggesting a potential tumor suppressive role. 39 The reason for discrepancy in these results is not clear, but a deeper investigation into different miRNA-29 family members would likely explain the varied reports.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study proposed that a high concentration of serum miRNA-29a-3p is associated with poor overall survival and progression-free survival in patients with HCC treated with resection or local ablation. 38 However, a contrasting study found miRNA-29 genetic (miRNA-29a-3p/b/c) expression was downregulated in HCC tissue suggesting a potential tumor suppressive role. 39 The reason for discrepancy in these results is not clear, but a deeper investigation into different miRNA-29 family members would likely explain the varied reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the levels of circulating miRNAs can be significantly altered at different physiological stages and pathological conditions. Specific circulating miRNA profiles have been reported for various diseases [ 11 , 13 16 ]. These circulating miRNA profiles have been described to correlate with differentially expressed miRNAs in diseased tissue, such as the liver following injury by drugs [ 29 ] or a related cancer [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNAs have been reported to be promising biomarkers for various pathologic conditions, including liver disease. Some miRNAs have been demonstrated to change after the initiation and progression of various liver diseases, such as CHB [ 13 , 14 ], HBC [ 15 ], and HCC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the following year, Zhu et al discovered the role of miR-29a as a prognostic marker in HCC patients receiving surgical resection [35]. At present, growing body of evidence has shown the significance of miR-29a as a diagnostic/prognostic tool in HCC [41,42,47,50,55,[67][68][69][70] and alcoholic liver disease [71], as well as NAFLD. In 2017, Lopez-Riera et al identified circulating miR-29a as one predictor of miRNAs biomarker set in NAFLD patients [72].…”
Section: Mirs As Markers In Liver Diseasementioning
confidence: 99%